Estudio de factibilidad para la creación de una empresa dedicada a comercializar café orgánico tostado y molido en el municipio de Armenia-Quindío (2009)
Organic, organic or biological agriculture frames all agricultural systems that promote the healthy and safe production of fibers and food, from an environmental, social and economic point of view. These systems start from the fertility of the soil as the basis for a good production. Without modifying the natural demands and capacities of plants, animals and the landscape, it seeks to optimize the quality of agriculture and the environment in all its aspects. Organic farming significantly reduces the need for external inputs by not using artificial fertilizers or pesticides. All processes applied to obtain an organic product must be guaranteed to consumers through a certification system. The growing concern of consumers in developed countries for the protection of the environment and health care, coupled with the frequent identification of foodborne diseases (ETAs), has been detrimental to consumers' confidence in conventional systems of food production and, simultaneously, have generated an increase in the demand for products of ecological origin.